C‐Reactive Protein Identifies Low‐Risk Metabolically Healthy Obese Persons: The European Prospective Investigation of Cancer–Norfolk Prospective Population Study - van Wijk, Diederik F. (J Am Heart Assoc, 2016)
BACKGROUND: Conflicting data exist about the cardiovascular risk of metabolically healthy obese persons. The prognostic value of C‐reactive protein (CRP) in this intriguing group is unknown. We assessed the association between CRP levels and the risk of coronary heart disease (CHD) in metabolically healthy persons with abdominal obesity. METHODS AND RESULTS: In the European Prospective Investigation of Cancer–Norfolk prospective cohort, CRP levels and information on metabolic syndrome criteria were available for 7279 participants, of whom 825 (11%) developed CHD during a follow‐up period of 10.9±1.8 years. There was a trend toward a higher multivariable‐adjusted hazard ratio for CHD in metabolically healthy obese participants with CRP levels >2 mg/L compared with <2 mg/L (hazard ratio 1.59, 95% CI 0.97–2.62, P=0.066). Metabolically unhealthy obese participants had significantly higher CHD risk compared with metabolically healthy obese participants with CRP levels <2 mg/L (hazard ratio 1.88, 95% CI 1.20–2.94, P=0.006). Most important, we found that the risk of CHD among metabolically healthy obese persons with CRP levels <2 mg/L was comparable to that of metabolically healthy nonobese persons (hazard ratio 0.91, 95% CI 0.60–1.39, P=0.674). CONCLUSIONS: Among metabolically healthy obese persons, low CRP levels were associated with a CHD risk comparable to that of metabolically healthy nonobese persons. CRP appears to be an easy and widely available method for identifying a low‐risk subpopulation among metabolically healthy obese persons.